Novel cyanate intercalated CoBi layered double hydroxide for ultimate charge separation and superior water splitting. (1st September 2021) - Mostafa, Mohsen S.; Chen, Lan; Selim, Mohamed S.; Betiha, Mohamed A.; Zhang, Ruiyi; Gao, Ya; Zhang, Shuai; Ge, Guanglu
Abstract: The discovered photocatalysts in the last decades didn't achieve the world great goal to get clean and renewable fuel by sunlight-induced water splitting, due to their low photoactivity-related wide bandgaps and working exclusively of the infrared (IR)-radiation that accounts for 53% of sunlight. In this work, we designed novel cyanate-intercalated CoBi layered double hydroxide (CICB-LDH) nanorods as highly active IR-photocatalyst by the one-pot inclusion of highly active (Bi n+ )-species with Co in an organic-inorganic hybrid nanocomposite. The synthesis route leads to the formation of abundant triple bonded (CN)-groups of superior trapping functions towards the photoexcited species, and in-turn elevated water splitting performance without the need for external scavengers. Based on the diffuse reflectance and X-ray photoelectron spectroscopy (XPS) analyses, CICB-LDH owns the narrower bandgap (1.32 eV) and much higher oxidation states of (Bi) compared to all the reported Co/Bi-structures, leading to superior photocatalytic activity. In the challenge oxygen evolution (OE)-reaction, CICB-LDH has achieved the maximum (OE)-rate of 5455 μmolg −1 h −1 without noble co-promoters. Stacking in 1D-assembly facilitates the CICB-LDH dispersion, inter-layer water diffusion, and the (IR)-transferring during the photocatalysis. In addition, CICB-LDH shows excellent structural and photochemical stabilities as a robust layered structure for futuristic clean fuel production. Graphical abstract: Image 1 Highlights: Novel cyanate intercalated CoBi LDH (CICB-LDH) was synthesized as IR-responsive. The responsive in 1D-assembly showed much higher oxidation states of Co and Bi. Maximum charge mobilities through short pathway were attained by CICB-LDH. High OE-rate (5455 μmolg −1 h −1 ) could be achieved by a narrow bandgap of 1.32 eV. 1D CICB-LDH is active and stable as cornerstone of the next IR-responsives.